2022
DOI: 10.1101/2022.12.23.519261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor Microenvironment Cellular Crosstalk Predicts Response to Adoptive TIL Therapy in Melanoma

Abstract: Adoptive cell therapy (ACT) using ex vivo expanded tumor-infiltrating T lymphocytes (TILs) can mediate responses in metastatic melanoma, but long-term efficacy remains limited to a fraction of patients. Here we interrogated tumor-microenvironment (TME) cellular states and interactions of longitudinal samples from 13 metastatic melanoma patients treated with TIL-ACT in our clinical study (NCT03475134). We performed single-cell RNA-seq and spatial proteomic analyses in pre- and post-ACT tumor tissues and showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…To gain insights into T-cell dynamics and the in vitro and in vivo fates of cells in the context of TIL-ACT, we interrogated deeply and longitudinally T cells in 13 metastatic melanoma patients who received TIL-ACT in a phase-I clinical trial (NCT03475134). The objective response rate (ORR) in this study was 46.2% (n=6/13) 25 . We examined, by integrated single-cell analyses, the profile of 122'000 T cells, and using bulk TCR-seq we tracked the dynamics of over 2.8x10 6 clonotypes.…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…To gain insights into T-cell dynamics and the in vitro and in vivo fates of cells in the context of TIL-ACT, we interrogated deeply and longitudinally T cells in 13 metastatic melanoma patients who received TIL-ACT in a phase-I clinical trial (NCT03475134). The objective response rate (ORR) in this study was 46.2% (n=6/13) 25 . We examined, by integrated single-cell analyses, the profile of 122'000 T cells, and using bulk TCR-seq we tracked the dynamics of over 2.8x10 6 clonotypes.…”
mentioning
confidence: 53%
“…The number of adoptively-transferred tumor-specific T cells predicts efficacy in preclinical models and clinical ACT studies [26][27][28] . For translational purposes, we classified patients as responders (Rs) when they had a complete or partial response (by RECIST criteria v1.1, n=6) vs. non-responders (NRs) when they experienced stable or progressive disease (n=7) 25 . We found that responding patients received more total T cells (Fig.…”
Section: Tumor-resident Cd8 + Vs Blood-borne Cd4 + Clonotype Enrichme...mentioning
confidence: 99%
See 2 more Smart Citations
“…Also for TIL therapy, first indications of the influence of the TME composition in generating TIL products have been collected. In melanoma patients, the T cell differentiation status was proposed to correlate with the efficacy of the TIL product 5,26 , and in a small cohort, a correlation with the activation status of macrophages and dendritic cells was observed 27 . For NSCLC-derived TIL products, such correlations with the immune cell infiltrates in tumor lesions have, to our knowledge, not yet been reported.…”
Section: Introductionmentioning
confidence: 99%